Genetic and pathogenicity diversity of dengue virus type 2 strains circulating in Guangdong, China - Lu Zhang; Lingzhai Zhao; Zhaoyong Zhang; Wenxin Hong; Jian Wang; Shuang Qiu; Huiqin Yang; Mian Gan; Jing Sun; Jingxian Zhao; Yanqun Wang; Jincun Zhao; et al. (Elsevier, 2021)
Dengue fever is a mosquito-borne viral disease spread in tropical and subtropical regions caused by the dengue virus (DENV). DENV causes a febrile illness, severe forms including hemorrhagic fevers and shock with fatalities in humans. DENV-2 is frequently associated with severe dengue infections and epidemics. DENV-2 strains from Guangdong, China, have not been characterized to compare the phylogenetics and pathogenicity of different DENV-2 subgenotype strains in both vitro and vivo. A total of 22 patients tested to be DENV-2 positive and were enrolled in this study, 22 complete genomes were obtained by virus isolation and high-throughput sequencing. Phylogenetic and single amino polymorphism (SAP) analysis indicated that two major subgenotypes (A and C) of DENV-2 Cosmopolitan were prevalent in Guangdong in 2018. The apparent change of major subgenotypes of DENV-2 circulating in Guangdong indicated the diversity of DENV-2 strains, including endemic genotype and imported genotype. It alerted the risk of cross-border transmission of DENV. A significant difference in replication rate was observed in C6/36 between different DENV-2 strains, although growth kinetics comparison of different DENV-2 Cosmopolitan subgenotypes showed similar profiles. DENV-2 subgenotypes (A and C) replicated efficiently in IFNAR−/− C57BL/6 mice, and subgenotype A of Cosmopolitan infected mice showed increased weight loss and delayed viral clearance compared with the subgenotype C group. DENV-2 prevalent in Guangdong in 2018 showed apparent genetic and pathogenicity diversity in both vitro and vivo, indicating the necessity of molecular surveillance and exploration of the relationship between its pathogenicity and clinical characteristics.